Adaptation - Lo, Malinda (Little, Brown, 2012)
In the aftermath of a series of plane crashes caused by birds, seventeen-year-old Reese and her debate-team partner, David, receive medical treatment at a secret government facility and become tangled in a conspiracy that is, according to Reese's friend, Julian, connected with aliens and UFOs.